2008
DOI: 10.1002/mus.20958
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion body myositis functional rating scale: A reliable and valid measure of disease severity

Abstract: We developed a disease-specific, 10-point functional rating scale for patients with inclusion body myositis (IBMFRS). The IBMFRS was utilized as a secondary outcome measure in a multicenter pilot trial of the clinical safety and tolerability of high-dose beta interferon-1a. In this trial, 28 IBM patients completed the IBMFRS at baseline and monthly for 6 months. The IBMFRS showed statistically significant correlations (P < 0.001) with maximal voluntary isometric contraction, manual muscle testing, handgrip dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
111
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 21 publications
0
111
1
Order By: Relevance
“…Quadriceps strength was also found to be a sensitive indicator of disease progression in a French patient cohort (Allenbach et al, 2012). In the UK-based IBM-Net Project to identify outcome measures for clinical trials, a 27.9% decline in strength was found with QMT at one-year follow-up in a group of 23 patients and a 13.8% annual decline in the 10-point IBM Functional Rating Scale (IBM-FRS) and it was concluded that QMT and the IBM-FRS are the best indicators of disease progression (Jackson et al, 2008, Cortese et al, 2013. A longitudinal study of 136 IBM patients from two European Centres used a composite clinical weakness index (ICWI) to assess progression in a subgroup of 71 patients, and found a good correlation with other measures of strength and walking handicap (Benveniste et al, 2011).…”
Section: Natural Historymentioning
confidence: 99%
“…Quadriceps strength was also found to be a sensitive indicator of disease progression in a French patient cohort (Allenbach et al, 2012). In the UK-based IBM-Net Project to identify outcome measures for clinical trials, a 27.9% decline in strength was found with QMT at one-year follow-up in a group of 23 patients and a 13.8% annual decline in the 10-point IBM Functional Rating Scale (IBM-FRS) and it was concluded that QMT and the IBM-FRS are the best indicators of disease progression (Jackson et al, 2008, Cortese et al, 2013. A longitudinal study of 136 IBM patients from two European Centres used a composite clinical weakness index (ICWI) to assess progression in a subgroup of 71 patients, and found a good correlation with other measures of strength and walking handicap (Benveniste et al, 2011).…”
Section: Natural Historymentioning
confidence: 99%
“…Disease severity was assessed by the IBM functional rating scale (IBM-FRS). [13] This scale assesses function across 10 activities of daily living scoring each from 0 (unable to perform) to 4 (normal). The closer the total score is to the maximum possible of 40 the better the functional status of the patient.…”
Section: Measurementsmentioning
confidence: 99%
“…The lack of blinding and placebo control will make it challenging to determine whether alemtuzumab administration, prophylactic antibiotic administration, or other aspects of patient and investigator nonblinded participation in this study (such as biased assessment of outcome) accounted for the results. Other recent articles address epidemiology [14], electrophysiology [15][16][17], the development of a functional rating scale as a research tool [18], and no susceptibility association with apolipoprotein E genotypes [19].…”
Section: Clinical Features and Treatmentmentioning
confidence: 99%